Effect of the inclusion of dry pasta by-products at different levels in the diet of typical Italian finishing heavy pigs: Performance, carcass characteristics, and ham quality. (April 2016) - Prandini, A.; Sigolo, S.; Moschini, M.; Giuberti, G.; Morlacchini, M.
Abstract: The effect of pasta inclusion in finishing pig diets was evaluated on growth performance, carcass characteristics, and ham quality. Pigs (144) were assigned to 4 diets with different pasta levels: 0 (control, corn-based diet), 30, 60, or 80%. Pigs fed pasta had greater (linear, P < 0.01) feed intakes than controls. Pasta increased (quadratic, P < 0.01) carcass weight and dressing percentage reaching the highest values at 30% inclusion level, and reduced (linear, P < 0.01) the Longissimus thoracis et lumborum thickness. Pasta decreased (linear, P < 0.01) linoleic acid and polyunsaturated fatty acid levels in subcutaneous (fresh and seasoned hams) and intramuscular (seasoned hams) fat, and enhanced saturated fatty acid content in subcutaneous fat (fresh hams: quadratic, P < 0.01; seasoned hams: linear, P = 0.03). Proteolysis index, colour, weight losses, and sensory properties (excepted extraneous taste) of the hams were unaffected by the pasta. Pasta could be considered as an ingredient in the diet for typical Italian finishing heavy pigs. Highlights: Dry pasta by-products were included in the diet for Italian finishing heavy pigs. The inclusion of pasta had no adverse effects on the growth performance. 30% pasta increased carcass weight and dressing %, and reduced LTL thickness. Pasta affected fatty acid profile but not sensory traits of the hams. Alternately to corn, pasta could be included in the diet for finishing heavy pigs.